SUMMARY OF MN TOBACCO LOBBYIST MEETING (Tufts Archival Research Center, 2007)
Memorandum from Alice O’Connor to Pat Donoho summarizing the Minnesota Tobacco Lobbyists meeting. Includes topics of excise taxes, privacy bills, and indoor air quality.